2021
DOI: 10.1186/s13287-021-02248-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from human placental mesenchymal stem cells enhanced the recovery of spinal cord injury by activating endogenous neurogenesis

Abstract: Background Spinal cord injury (SCI) is a debilitating medical condition that can result in the irreversible loss of sensorimotor function. Current therapies fail to provide an effective recovery being crucial to develop more effective approaches. Mesenchymal stem cell (MSC) exosomes have been shown to be able to facilitate axonal growth and act as mediators to regulate neurogenesis and neuroprotection, holding great therapeutic potential in SCI conditions. This study aimed to assess the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…It has been reported that MSCs from WJ and BM release several factors that promote neurogenesis, but WJ-MSCs expressed more genes associated with neurogenesis [ 55 ]. Exosomes from MSCs also promoted neurogenesis in animal models of Alzheimer disease [ 54 ] and traumatic brain injury [ 56 ] and can enhance recovery in the case of spinal cord injury [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MSCs from WJ and BM release several factors that promote neurogenesis, but WJ-MSCs expressed more genes associated with neurogenesis [ 55 ]. Exosomes from MSCs also promoted neurogenesis in animal models of Alzheimer disease [ 54 ] and traumatic brain injury [ 56 ] and can enhance recovery in the case of spinal cord injury [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sun et al demonstrated that the sub-acute co-transplantation of human NSC and MSC enhanced stem cell survival compared to individual treatments, increased the number of myelinated axons, and improved locomotor function [ 52 ]. The use of MSC secretome, alone or in combination with NSC, would provide a successful alternative to cell therapy, since researchers have ascribed paracrine effects to exosomes in the treatment of spinal cord injuries including anti-inflammatory [ 53 ], angiogenic [ 54 ] and regenerative effects [ 55 ], as well as functional recovery [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the included 32 studies, only two studies were controlled studies (29,33), and the remaining 30 studies were randomized controlled studies. The species of animals included SD rats (19-21, 28-37, 39, 40, 42-44, 46, 47, 49-53, 55, 56), Wistar rats (41,54), and C57BL/6 mice (38,45,48); gender included male (28, 30-32, 38-45, 49, 53, 54) and female (19, 20, 29, 33, 34, 36, 37, 46-48, 50-52, 55, 56), two studies did not report the sex of the animals (21,35); the weights of animals were between 150 (41) and 300 g (20,44), the weight of the mouse was between 17 and 22 g ( 48), and seven of the studies did not report the weight of the animals (21,29,30,38,42,45,50); age was between 6 (38,44,45,50,51) and 12 weeks (47, 56), and nine of the studies did not report the age of the animals (19, 21, 35-37, 42, 46, 51, 52); samples size were between 10 (51) and 100 (41); models of SCI included contusion (20, 21, 28-32, 34-53, 56), hemisection (54), and transection (19,33,55); the types of exosomes included the exosomes of bone marrow mesenchymal stem cells of SD rats (BMSCs-Exo) (20, 21, 28, 30, 34-37, 39, 42-44, 47, 49, 52, 53, 56), BMSCs-Exo of Wistar rats (41,54), BMSCs-Exo of human (19,33,…”
Section: Basic Information For Inclusion In the Studymentioning
confidence: 99%